1900 N.Y. Laws 756, ch. 338, art. 3, § 32, pt. 12. - (:unkn) unknown (General Publisher, 1900)
To regulate or prevent the discharge of firearms, rockets, gunpowder or other explosives, or the making of bon-fires.
--
Keywords: DISCHARGE